2005
DOI: 10.1007/s11255-004-7135-5
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Serum Magnesium Level in Haemodialysis Patients Receiving Sevelamer Hydrochloride

Abstract: Our findings indicate that patients on haemodialysis receiving sevelamer have a significant increase in serum magnesium concentrations. This increase in serum magnesium is associated with reduction in iPTH levels. The changes in lipid profiles of these patients however are not related to changes in serum magnesium levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…They found that HD patients receiving sevelamer have a significant increase in serum Mg. This increase in serum Mg is associated with a reduction in the iPTH level (r = -0.40, p = 0.016) [84] . It can be speculated that the rise in serum Mg levels might also contribute to the much debated superiority of sevelamer in suppressing vascular calcifications compared to other phosphate binders.…”
Section: The Effect Of Mg On Athero-and Arteriosclerosis: Vascular Camentioning
confidence: 91%
See 1 more Smart Citation
“…They found that HD patients receiving sevelamer have a significant increase in serum Mg. This increase in serum Mg is associated with a reduction in the iPTH level (r = -0.40, p = 0.016) [84] . It can be speculated that the rise in serum Mg levels might also contribute to the much debated superiority of sevelamer in suppressing vascular calcifications compared to other phosphate binders.…”
Section: The Effect Of Mg On Athero-and Arteriosclerosis: Vascular Camentioning
confidence: 91%
“…The authors concluded that 'hypermagnesemia might be associated with retardation or improvement of arterial calcifications in peritoneal dialysis patients' [64] . Finally, Mitsopoulos et al [84] investigated the effect of sevelamer on serum Mg in HD patients to assess the association of Mg levels with iPTH and lipid profiles. They found that HD patients receiving sevelamer have a significant increase in serum Mg.…”
Section: The Effect Of Mg On Athero-and Arteriosclerosis: Vascular Camentioning
confidence: 99%
“…It seems plausible to speculate that this effect of sevelamer depends on its adsorptive action on some substances other than P. Free fatty acids in the intestinal lumen may combine with Mg to form non-absorbable soaps. Therefore, Mitsopoulos et al speculated that sevelamer binds biliary salts, thereby increasing the quantity of free Mg available for intestinal absorption [84]. On the other hand, Nagano et al reported the contribution of magnesium stearate, which is included as a pharmaceutical excipient in phosphate binders, to increases in serum Mg levels [87].…”
Section: Mg-containing Laxativesmentioning
confidence: 99%
“…It is well tolerated except for an increased incidence of metabolic acidosis [7]. Other side effects include abdominal pain, diarrhea, nauseavomiting, muscle cramps, hypocalcemia, headache and hypermagnesemia [8]. In children with end stage renal disease, it has been used in doses of 100 mg/kg/day to 130 mg/kg/day, every 8 hours [7,9].…”
Section: Discussionmentioning
confidence: 99%